The Relationship between Anxiety Level and Sleep Quality on 11th Grade Student of Kharisma Bangsa High School and its Review According to Islamic Views - Sandrina Shera Monifa; Sri Wahyu Herlinawati; Firman Arifandi (Junior Medical Journal, 2022)
Introduction : Anxiety is a common thing in human life. Anxiety disorders are one of the problems that can arise at any time and can be experienced by everyone including adults, teenagers or children who are following the learning process at school (Mukholil, 2018). The results of the Basic Health Research (Riskesdas) in 2018, the prevalence of anxiety disorders in Indonesia showed that as many as 6% aged 15 years and over or around 14 million people in Indonesia experienced emotional mental disorders such as anxiety disorders. Generally, adolescents who have mild anxiety disorders have psychosomatic symptoms, if not handled properly it can have a bad impact that can cause a person to experience anxiety when they want to sleep.Methods: This research uses analytical research with a cross sectional research design. The sample was determined using a random sampling technique with a total sample of 85 respondents. Data collection was done by filling out a questionnaire. Data analysis with Chi-Square Test using SPSS version 25.0.Results: The results showed that there were 35 respondents (68.6%) who experienced feelings of anxiety in class XI students of SMA Kharisma Bangsa and 40 respondents (78.4%) who had poor sleep quality and 11 respondents (21.6%) others. have good sleep quality in class XI students of SMA Kharisma Bangsa. Based on the Chi-Square Test, p value = 0.009 which states that there is a relationship between the level of anxiety and sleep quality in high school students XI Kharisma Bangsa. Conclusion: There is a significant relationship between anxiety levels and sleep quality in class XI students of SMA Kharisma Bangsa. Suggestions that can be given are to maintain the level of anxiety and sleep quality by paying attention to the factors that can affect these two things